KEMAMPUAN ADAPTASI KEPITING BAKAU (Scyla serrata) TERHADAP PERUBAHAN SALINITAS AIR - Retno Widaningroem; Alim Isnansetyo (Jurnal Perikanan Universitas Gadjah Mada, 1996)
Objectives of this research were to know water salinity change which can be use for culturing and fattening of mud crab, and to know adaptation of mud crab on water salinity change. The research used modified bioassay method and completely randomized factorial design consisted of two factor namely water salinity change (0,5 and 10 ppt of water salinity change) and duration of water salinity change (3 and 6 hours).The result indicated that decreasing salinity by 5 and 10 ppt per 3 and 6 hours from 20 to 0 ppt could be adapted by mud crab. As well as increasing if salinity by 5 and 10 ppt per 10 and 6 hours from 20 to 5 ppt could be adapted by mud crab. Mud crab was able to adapt water salinity change by 5 and 10 ppt per 3 and 6 hours from 0 to 50 ppt.